EFFICACY OF PRE-OPERATIVE INJECTION MITOMYCIN-C IN PREVENTION OF PTERYGIUM RECURRENCE: Prevention of Pterygium Recurrence - Khan, Muhammad Dawood; Shoaib, Khwaja Khalid; Hamid, Shahid; Ali, Kashif; Ali, Saqib; Sadiq, Muhammad Asif (Pakistan Armed Forces Medical Journal, 2008)
Objective: To determine the recurrence rate of pterygium with four weeks pre-operative injection mitomycin-C using bare sclera technique.Design: An interventional case series.Place and Duration of Study: This ongoing study was started in November 2005 at eye department of combined military hospital Kharian, Pakistan.Patients and Methods: Ninety one eyes of 87 patients have been so far enrolled in the study. Cases between 20 to 50 years of age, of either sex, with primary and recurrent pterygia were included. The subjects were first given 0.1 ml injection mitomycin-C 0.15 mg/ml into the body of pterygium. Four weeks later, pterygium surgery was performed using bare-sclera technique. The subjects are being followed up for at least one year to detect any recurrence.Results: Out of 91 cases, 16 (17.58%) cases have been followed up for 12 months, 19 (20.87%) for 9 months, 21 (23.07%) for 6 months, 17 (18.68%) for 3 months and 18 (19.78%) for less than 3 months. Recurrence has not been encountered in any of these cases so far. Conclusion: Initial results show that pterygium surgery with pre-operative injection mitomycin-C appears to be an effective form of treatment for prevention of pterygium recurrence. Further follow up and multi-centric studies are required for final conclusion.